ANALYSIS OF BLOCKCHAIN UTILIZATION IN ZAKAT MANAGEMENT: ENHANCING TRANSPARENCY AND TRUST - Muhammad Anwar Sani; Marzuki Marzuki; Nur Diana Dewi (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2026)
This study aims to develop a blockchain model as an effective instrument for zakat management. The method employed in this research is a qualitative method with a grounded theory approach. In-depth interviews were conducted with several stakeholders to confirm the feasibility of blockchain in zakat management. Subsequently, the data were analysed using the Atlas.ti tool. The results of this study indicate that there are five main dimensions forming the blockchain model for zakat it was trust mechanisms, transparency, accountability, cost and efficiency, and distribution speed. Test results revealed dimensions in the form of trust mechanism, transparency, cost and efficiency, record keeping, and distribution speed. The study argues that blockchain's value in zakat management lies not merely in technical automation but in operationalizing Islamic principles of justice and accountability in recording while clarifying that blockchain implementation for zakat is distinct from cryptocurrency and does not conflict with Indonesia's currency regulation. The study recommends future quantitative validation of the proposed model and the development of a regulatory framework to support blockchain adoption in Islamic social finance.